Resveratrol-βcd inhibited premature ovarian insufficiency progression by regulating granulosa cell autophagy - Bingbing Hu; Xiushuang Zheng; Wei Zhang (Journal of Ovarian Research, 2024)
Abstract Background The ovarian environment of premature ovarian insufficiency (POI) patients exhibits immune dysregulation, which leads to excessive secretion of numerous proinflammatory cytokines that affect ovarian function. An abnormal level of macrophage polarization directly or indirectly inhibits the differentiation of ovarian granulosa cells and steroid hormone production, ultimately leading to POI. Resveratrol, as a health supplement, has been widely recognized for its safety. There is a substantial amount of evidence indicating that resveratrol and its analogs possess significant immune-regulatory functions. It has also been reported that resveratrol can effectively inhibit the progression of POI. However, the underlying immunological and molecular mechanisms through which resveratrol inhibits the progression of POI are still unclear. Results Our preliminary reports have shown that resveratrol-βcd, the beta-cyclodextrin complex of resveratrol, significantly enhances the stability of resveratrol. Resveratrol-βcd could regulate the dysfunctional immune status of macrophages and T cells in the tumor microenvironment. In this study, we treated busulfan and cyclophosphamide (B/C)-treated mice, which were used as a POI model, with resveratrol-βcd. After resveratrol-βcd treatment, the levels of IL-6 in the ovaries were significantly increased, and the progression of POI was suppressed. IL-6 activated granulosa cells (GCs) through soluble IL-6R (sIL-6R), promoting autophagy in GCs. Resveratrol-βcd and IL-6 had a synergistic effect on enhancing autophagy in GCs and promoting E2 secretion. Conclusions We partially elucidated the immune mechanism by which resveratrol inhibits the progression of POI and the autophagy-regulating function of GCs. This provides a theoretical basis for using resveratrol to prevent POI in future studies and clinical guidance.